Membaca Kritik Seni dalam Film ‘Like and Share’ Tahun 2022: Realitas Sosial dalam Industri Kapitalis - Amalia Latifah; Emillia Della Maulina (Besaung : Jurnal Seni Desain dan Budaya, 2024)
The current issue in capitalist societies is the social decisions that often lead to gender imbalance perspective towards women, viewing them as objects or enjoyment for those who hold such equal perspective. Film is one of the reliable mediums for artistic critique that can convey this discourse to today’s younger generation. Therefore, this research analyses the film “Like and Share” (2022) as a representation of artistic critique of the social reality in capitalist society. This film portrays various aspects of social reality due to the gender inequality perspective in capitalist society, such as patriarchal culture, gender stereotypes, women’s exploration, rape culture, and the influence of religion in daily life. The research method used is qualitative with descriptive analysis of scenes and dialogues in the film. The result shows that this film successfully reflects the social reality of capitalist society and the influence of capitalism in the film industry. Thus, this film is effective as a medium of artistic critique of the social reality of capitalist society in the context of the Indonesian film industry. Keywords: art critique, social realities, capitalist industry, Like and Share